The effect of linking community health centers to a state-level smoker's quitline on rates of cessation assistance - Cantrell Jennifer; Shelley Donna (BMC, 2010)
Abstract Background Smoking cessation quitlines are an effective yet largely untapped resource for clinician referrals. The aim of this study was to assess the effect of a fax referral system that links community health centers (CHCs) with the New York State Quitline on rates of provider cessation assistance. Methods This study was conducted in four CHCs using a quasi experimental study design. Two comparison sites offered usual care (expanded vital sign chart stamp that prompted providers to ask about tobacco use, advice smokers to quit, assess readiness, and offer assistance (4As)) and two intervention sites received the chart stamp plus an office-based fax referral link to the New York State Quitline. The fax referral system links patients to a free proactive telephone counseling service. Provider adherence to the 4 As was assessed with 263 pre and 165 post cross sectional patient exit interviews at all four sites. Results Adherence to the 4As increased significantly over time in the intervention sites with no change from baseline in the comparison sites. Intervention sites were 2.4 (p < .008) times more likely to provide referrals to the state Quitline over time than the comparison sites and 1.8 (p < .001) times more likely to offer medication counseling and/or a prescription. Conclusions Referral links between CHCs and state level telephone quitlines may facilitate the provision of cessation assistance by offering clinicians a practical method for referring smokers to this effective service. Further studies are needed to confirm the efficacy of fax referral systems and to identify implementation strategies that work to facilitate the utilization of these systems across a wide range of clinical settings.